We Need to Talk: A Memoir About Wealth - Risher, Jennifer, 1965- (Book collections on Project MUSE., 2020)
"We Need to Talk: A Memoir About Wealth gives voice to an experience millions share, but no one discusses: what it's like to be rich. The book is an honest, personal story that explores the hidden impact of wealth on identity, relationships, and sense of place in the world. Too often, we link net-worth to self-worth and keep quiet about how our finances make us feel. Money is a taboo subject. The author hopes We Need to Talk becomes a catalyst for conversation that demystifies wealth, gets us talking on a personal level, and confirms we are ninety-nine percent the same. In 1991, at twenty-six years old, Jennifer took a job at Microsoft and got lucky. She met her future husband, David, and the stock options she was granted were worth hundreds of thousands of dollars. His were worth far more. Years later, when David joined a small, unknown start-up called Amazon.com, she got lucky again. They both did. They were in their early thirties and had tens of millions of dollars. It was amazing. The freedom and benefits were obvious. But after growing up saving her pennies and being wary of the rich, Jennifer was embarrassed to have joined their ranks. She wasn't worried about being liked for her money, she was worried about being hated for it. People looked at her differently. She didn't know how to ensure her children stayed motivated and not entitled, was shocked when a friend asked for $25,000, discovered philanthropy isn't as straightforward as just writing a check, and grappled with the meaning of enough. For years, she didn't share her dilemmas with others for fear of being judged. No one talks about money-but we should." --